Perbandingan kadar kreatinin darah antara penderita preeklampsia berat/eklamsia dengan kehamilan normal - Rushakim Lubis; Ichwanul Adenin; M. Rhiza Z Tala (Fakultas Kedokteran USU, 2017)
Introduc : Comparison analysis blood level of creatinine in severe preeclampsia/eclampsia with normal pregnancy. This study is an observational analytic study with a cross-sectional study design to pregnant women in severe preeclampsia/eclampsia and pregnant women with normal blood pressure. .Results : In this study, which began in April 2014, 30 patients obtained eclampsia and severe preeclampsia. Characteristics of pregnant women with severe preeclampsia/eclampsia highest in the age group 20-35 years (41.7%). Based on the number of pregnancies, with gravid 1 is 25% the same as much as 25% gravida 2-3. History of education, which is the highest with low education (40 %), the highest number of ANC visit < 4 times as much as 35%. There is no significant difference in creatinine blood level between pregnancy in severe preeclampsia/ eclampsia with normal pregnancy, where the p value is worth < 0.605 (p> 0.05).Conclusions : There is no significant difference in creatinine blood level between pregnant mother in severe preeclampsia with normalapregnancy. .Keywords : Severe preeclampsia, Eclampsia, Creatinine